What's going on down (under) there? Unravelling biochemical flows under differential rainfall periods in a Western Australian calcrete - Sacco, Mattia; Blyth, Alison; Meredith, Karina; Smith, Colin; Hua, Quan; Mazumder, Debashish; Humphreys, William F; White, Nicole; Grice, Kliti (2019)
Groundwater is a vital resource. It contains 97% of unfrozen water on the planet, playing a key role in present and future water needs for humanity. However, our knowledge about the ecosystem functioning is very poor, and groundwater environments are increasingly exposed to anthropic impacts and climate change related processes. Novel biochemical (e.g. isotopic ecology) and genetic (e.g. eDNA) techniques, widely employed in fresh surface water studies, have the potential to unravel the complex dynamics shaping subsurface ecosystems, providing new insights to the small but quickly growing field of groundwater ecology. Stygofauna, together with microbes, are crucial actors in shaping and maintaining the organic matter (OM) cycles in environments characterized by low energy and scarce carbon availability. In order to understand groundwater ecological patterns, we investigate calcrete stygofaunal shifts linked with contrasting rainfall periods (low rainfall (LR), dry season; high rainfall (HR), wet season), through an interdisciplinary design composed of hydrology, isotopic ecology and genetics. Our results indicate that the inflow of rainfall under HR is responsible for increased nutrient concentrations in the system and dissolved organic carbon (DOC) pulses from the surface. Both the meiofaunal and stygofaunal communities’ benefit from these organic inflows, with gamma and proteobacteria the biota that fuels carbon and nutrients to the higher levels of the trophic web. The HR regime - and its subsequent terrestrial carbon incorporation - triggers a cascade effect driven by microbes (OM processors) and amphipods (biofilm grazers), which is finally transferred to the aquatic beetles (top predators). Overall, and in line with other work in the same research area, the inflow of rainfall triggered shifts towards more deterministic dynamics, revealing a complex web of interactions in a seemingly simple environmental setting. This study provides a preliminary untangling of the biochemical flows driven by rainfall in a calcrete aquifer. More investigations involving multidisciplinary approaches on other subsurface ecosystems, i.e. alluvial aquifers, will help to understand present ecological patterns and predict future scenarios in groundwaters.